Soul color : a ten week watercolor course to cultivate mindfulness and creativity - Burleigh, Emma (New York, NY : Liminal, 2021)
Soul Color is a ten-week watercolor painting course designed to cultivate mindfulness and creativity. Develop confidence to paint more intuitively, give yourself permission to enjoy the unexpected and make mistakes, deepen your meditation skills, and discover a new sense of reflective calm. Soul Color isn't a traditional how-to book. It is the outcome of several years of research and trial and error with students and friends who've come to Emma's workshops and classes.
Keywords: Watercolor painting -- Technique; Watercolor painting -- Technique